Generation of empty cell envelopes of Streptococcus pyogenes using biosurfactants - Amany Abdelfattah; Heba M. Amin; Sameh Rabea; Reham Samir (SpringerOpen, 2024)
Abstract Background Bacterial ghost cells (BGCs) are cell envelopes that devoid of cytoplasmic and genetic contents in purpose of variable applications, including their great potential as vaccine candidates and their effectiveness as delivery systems for drugs and proteins. To our knowledge, this is the first study to produce Gram-positive BGCs by treating Streptococcus pyogenes (S. pyogenes) ATCC 19615 with Tween80 (TW80) or TritonX-100 (TX100), followed by preliminary testing of their antigenicity and safety in NIH/Ola-Hsd mice. The produced BGCs were confirmed by the presence of intact cells under a light microscope, the absence of growth signs upon re-cultivation. The transmembrane tunnels were visualized using a scanning electron microscope, and subsequently, considerable quantities of released DNA and protein were detected in the culture supernatant of the BGCs. The antigenicity of the produced BGCs was tested through three intra-nasal immunization doses followed by infection. Afterward, the opsonic activity and the IgG levels were measured, followed by a comprehensive histopathological examination for selected tissues and organs. Results The sera of immunized mice exhibited a significant rise in both opsonic activity (TW80 produced BGC = 68% and TX100 produced BGC = 75%) and IgG levels (TW80 produced BGC = a threefold increase and TX100 produced BGC = a fourfold increase) when compared to the positive control group "non-immunized challenged with ATCC 19615." Histopathological analysis revealed that the BGCs produced by TW80 are relatively safer and have a less severe impact than those produced by TX100. Conclusion The study's findings suggest that Sp-BGC/TW80 is initially effective and safe in vivo. However, further pre-clinical studies are necessary to confirm its effectiveness and ensure complete safety, specifically in terms of the absence of autoimmunity and antibody cross-reactivity with myosin proteins in human cardiac tissues.